THE EFFECT OF REMPA KETA LACTATION MASSAGE ON BREAST MILK PRODUCTION AMONG POSTPARTUM MOTHERS IN THE EARLY PERIOD (0-7 DAYS) AT THE POSTPARTUM ROOM OF BIMA CITY HOSPITAL - Sri Hartati; Suseno, Mutiara Rachmawati; Ati Sulianty (Universitas STRADA Indonesia, 2024)
Background: Several methods have been researched to increase breast milk production. In Bima, many local cultural practices have been passed down to help address the issue of insufficient breast milk production. However, there is still a lack of research on the subject, which weakens the supporting evidence. Method: This research used a quasi-experimental. The sample consisted of 30 individuals, with 15 in the intervention group and 15 in the control group, selected through purposive sampling. The data was analyzed using the chi-square test. Result:Results of chi square test showed that when p < α = 0.05, there is an influence of Rempa Keta lactation massage on the smoothness of breast milk production in early postpartum mothers. Analysis : Data was analyzed using the chi-square test Conclusion: There is an influence of Rempa Keta lactation massage on the smoothness of breast milk production in early postpartum mothers (0-7 days).